2001
DOI: 10.1592/phco.21.13.1107.34613
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective and Retrospective Analysis of the Nephrotoxicity and Efficacy of Lipid‐Based Amphotericin B Formulations

Abstract: No significant differences in nephrotoxicity or efficacy were found between ABLC and L-AmB. Until further studies indicate clinically significant differences in nephrotoxicity between the two liposomal amphotericin B formulations, it is recommended that economics continue to be the major determinant for product selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…1,3,4 Amphotericin B is a broad-spectrum, effective antifungal agent, but its use is associated with nephrotoxicity and infusion-related side effects. 5,6 To date, no efficient salvage therapy has been available if amphotericin B fails to clear the infection, or if the patient is intolerant to amphotericin B.…”
Section: Invasive Fungal Infectionmentioning
confidence: 99%
“…1,3,4 Amphotericin B is a broad-spectrum, effective antifungal agent, but its use is associated with nephrotoxicity and infusion-related side effects. 5,6 To date, no efficient salvage therapy has been available if amphotericin B fails to clear the infection, or if the patient is intolerant to amphotericin B.…”
Section: Invasive Fungal Infectionmentioning
confidence: 99%
“…[4][5][6] Therapeutic decisions for these patients are difficult and it is not always possible to maintain an acceptable balance between toxicity and efficacy with commonly used antifungal regimens for IA. [7][8][9] Caspofungin is an exception in that, it has proven not only to be effective against IA, but has been well tolerated even among patients who were intolerant to or failed previous therapy. [9][10][11] The objective of this study was to evaluate caspofungin as first-line therapy in the treatment of proven and probable IA in patients who had received allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the other studies -which provided comparison between the two agents-revealed contradicting results. While McKechnie M et al (7) , Couch K et al (8) , Slain et al (9) ,Fleming et al (10) and Wingard et al (11) concluded that ABLC had higher renal side effects, interestingly enough, other researchers such as Lopez Sastre et al (12) ,McTaggartet al (13) ,Cannon et al (14) and fortune et al (15) reported the opposite. Out of those studies, the Pappas, et al study seemed to include the largest number of patients.…”
Section: Resultsmentioning
confidence: 99%